Industrial training report: Petrofac Malaysia - Ibrahim, Nurain Aqilah (Universiti Teknologi MARA, Perlis, 2024)
Executive summary for this report is about my 6 month industrial training at Petrofac Malaysia within Human Resources and Administration Department. Duration of my internship was 6 month which is started on 1st March 2024 until 9th August 2024. This is internship is one of the most important requirement in my studies in Human Resources Management for this semester.Following the placement for industrial training, students are urged to take part in all activities and fulfill all duties related to their industrial training experience. Students will be able to demonstrate their abilities and get them ready for areal working environment in the future.